Infective endocarditis initially manifesting as pseudogout. Issue 4 (4th July 2021) - Brotherton, Tim; Miller, Chad S.
Abstract: Infective endocarditis is a commonly encountered disease in which diagnosis is often challenging due to the variety of clinical manifestations. Early identification is key due to risk of mortality without treatment. In this case, a 31-year-old man presented with pseudogout of the right ankle and COVID-19 infection. Further workup showed blood cultures growing Staphylococcus aureus, and the diagnosis of infective endocarditis was confirmed by echocardiography. Independently, pseudogout and infective endocarditis result in activation of the innate immune system and can manifest with joint inflammation. Their co-occurrence likely resulted in an augmented inflammatory response due to overlap in their pathophysiologic pathways.